Análise dos Padrões Espaciais e Demográficos dos Benefícios da Aposentadoria Rural no Estado de Goiás (Élisée - Revista de Geografia da UEG, 2018)
Resumo: O artigo avalia a relevância dos benefícios monetários da Aposentadoria Rural no Estado de Goiás a partir da correlação entre o padrão de desenvolvimento regional e a demografia dos municípios. Os benefícios da Aposentadoria Rural, além de capitalizar as propriedades rurais, dinamizam o varejo urbano e contribuem para a redução da pobreza, especialmente na terceira idade.Palavras-chave: Aposentadoria Rural. Dinâmica econômica regional. Goiás.Spatial and Demographic Pattern Analysys of Rural Retirements Benefits in the State of GoiásAbstract: The article assess the relevance of monetary benefits of Rural Retirement in the State of Goiás from the correlation between the regional development pattern and the demography of municipalities. The benefits of Rural Retirement capitalizes the rural properties and bring dynamism to urban retail, as well contribute to reducing poverty, mainly in the old age.Keywords: Rural retirement. Regional economic dynamics. Goiás.